Kacapi Jeletot sebagai Manifestasi Kreativitas Seniman Karawang - Asep Wadi; Seftiyana, Gelar (LP2M ISBI Bandung, 2025)
Sundanese Kacapi is a functional instrument and can be independent, because it can accompany songs, control rhythmically, as well as create a melody in the song. Sundanese Kacapi is divided into three models namely; kacapi kawih, kacapi tembang, and kacapi celempung. However, apart from these three models, there is one model that is quite eccentric because the kacapi instrument used functions as a substitute for Sundanese drums with the Jaipongan genre. The kacapi presentation model is the creativity of an artist from Karawang, Ali Gombel, who is a kacapi celempungan artist. Until now, Ali Gombel's creativity has been able to survive and become a separate color from other kacapi presentation models. But basically kacapi jeletot is a typical art of Karawang Regency, West Java, and has become one of the identities of Karawang Regency in the performing arts sector. This research refers to the existence of kacapi jeletot which is one of the identities in the performing arts sector in Karawang Regency. This research uses the Miles and Huberman qualitative method using Rahayu Supanggah's garap theory and James P Burke's identity theory. The result of this research is that it can record the history of the art of kacapi jeletot from the start of its function, position, and the period of its spread in Karawang Regency as a form of cultural wealth in the performing arts sector. In addition, this research also transfers the creativity or kacapi work produced by Ali Gombel which was passed down to Toin Paser, because it can color the repertoire of kacapi accompaniment models by producing different kacapi accompaniment patterns as usual. This research can be a reference for artists in presenting kacapi instruments, and is expected to be one of the academic foundations for art research, especially Sundanese art.